2011
DOI: 10.1158/1078-0432.ccr-11-1066
|View full text |Cite
|
Sign up to set email alerts
|

PRAME-Specific Allo-HLA–Restricted T Cells with Potent Antitumor Reactivity Useful for Therapeutic T-Cell Receptor Gene Transfer

Abstract: Purpose: In human leukocyte antigen (HLA)–matched stem cell transplantation (SCT), it has been shown that beneficial immune response mediating graft-versus-tumor (GVT) responses can be separated from graft-versus-host disease (GVHD) immune responses. In this study, we investigated whether it would be possible to dissect the beneficial immune response of allo-HLA–reactive T cells with potent antitumor reactivity from GVHD-inducing T cells present in the detrimental immune response after HLA-mismatched SCT. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 36 publications
3
124
0
1
Order By: Relevance
“…This is reflected by the emergence of antigen-specific CD8 þ T cells in the peripheral blood of AML patients following transplantation. Such CTL responses have been reported against a broad range of AML-related tumor antigens, including HOXA9 (HOXA9 146-154 ), 62 hTERT (hTERT 540-548 ), 62 27,62 and RAGE-1 (RAGE-1 [11][12][13][14][15][16][17][18][19][20] (Table 1). 79 NuSAP1 has been identified as a target of humoral immunity following allogeneic HSCT.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 82%
See 1 more Smart Citation
“…This is reflected by the emergence of antigen-specific CD8 þ T cells in the peripheral blood of AML patients following transplantation. Such CTL responses have been reported against a broad range of AML-related tumor antigens, including HOXA9 (HOXA9 146-154 ), 62 hTERT (hTERT 540-548 ), 62 27,62 and RAGE-1 (RAGE-1 [11][12][13][14][15][16][17][18][19][20] (Table 1). 79 NuSAP1 has been identified as a target of humoral immunity following allogeneic HSCT.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 82%
“…26 Moreover, it was recently shown that PRAME-specific T cells may recognize normal kidney epithelial cells and dendritic cells. 27 On the opposite end of the spectrum are ubiquitous antigens, which are not only expressed in leukemic cells, but also in a wide variety of normal human tissues. Examples of such antigens are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, this relation was demonstrated in more than 50 other cancer cell lines as well. 9,16 We hereby proofed that mRNA expression leads to the expression of the relevant PRAME peptide because PRAME-T-cells could only have recognized the sarcoma cells if the PRAME peptide was processed by the proteasome and presented in the context of HLA-I. Whether a full length and functional protein is transcribed as well is not certain, but not relevant either, because expression and processing of the 9-amino acid long peptide is enough for T-cell recognition.…”
Section: Discussionmentioning
confidence: 99%
“…9 The PRAME specific TCR of HSS1 is currently used for the treatment of refractory or relapsed acute myeloid leukemia in a Phase I TCR-gene therapy trial (ClinicalTrials.gov NCT02743611). Controls included T-cell clone HSS12 recognizing peptide FTWEGLYNV from the ubiquitously expressed gene USP11 in the context of HLA-A*02:01 to confirm HLA-A*02:01 expression, 9 and the negative control clone pp65-A2, 29 also HLA-A*02:01-restricted, recognizing an antigen from cytomegalovirus (CMV), that is not expressed in sarcoma cells. T-cells were co-incubated with sarcoma cell lines and primary SS cells at responder-to-stimulator ratios of 1:4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation